The effectiveness and influencing factors of the “Y” line technique in reducing the leg length discrepancy after total hip arthroplasty - Wenshu Jin; Wenshu Jin; Huaqiang Sun; Xudong Duan; Xudong Duan; Yange Gu; Yange Gu; Zhang Zhao; Xinfeng Yan (Frontiers in Surgery, 2023)
ObjectiveTo introduce a surgical technique (the “Y” line technique) that will control leg length discrepancy (LLD) after total hip arthroplasty and to observe its effectiveness and influencing factors.MethodsAccording to the inclusion and exclusion criteria, a total of 350 patients were selected in this study; 134 patients in whom used the “Y” line technique was used to control lower limb length were included in Group A and 166 patients treated with freehand methods to control lower limb length were included in Group B. A total of 50 patients in whom the standard anteroposterior x-ray of bilateral hips was taken preoperatively and in whom the “Y” line technique was used during the operation were included in Group C.ResultsThe postoperative LLD of Group A was 4.74 mm (3.93), that of Group B was 5.85 mm (4.60), and that of Group C was 2 mm (1.00)—the difference was statistically significant (p < 0.001). There were significant statistical differences when comparisons were made between any two groups (p < 0.01). The distribution of postoperative LLD in Group A was better than that in Group B, and this factor was better in Group C than in Group A—the difference was statistically significant (p < 0.001). Severe unequal length rates of the lower extremities (LLD > 10 mm) were 5.97% (8/134) in Group A, 14.3% (24/166) in Group B, and 0% (0/50) in Group C—the difference was statistically significant (p < 0.001). There were significant differences between Group A and Group B and between Group B and Group C (p < 0.05), but there was no significant difference between Group A and Group C (p = 0.078).ConclusionThe “Y” line technique, which does not increase the operating time and patient cost, can effectively reduce postoperative LLD. Insufficient internal rotation of the healthy lower extremity and the low projection position in the preoperative anteroposterior x-ray of the bilateral hips were important factors affecting the accuracy of the “Y” line technique.